Práticas de cuidado popular de pessoas com úlcera venosa: implicações para a enfermagem - Rizzatti, Salete de Jesus Souza (2014)
The venous ulcer is defined as a chronic injury present in the lower third of the legs. It affects the individuals of different age ranges and it is associated to chronic venous insufficiency. It has importance from social and clinic point of view because it compromises their productivity and life quality. So, it becomes a challenge for the health team caring people who have venous ulcer due to its complexity and socio-economical repercussion. Therefore it is essential to create a link with the individual and his/her family promoting the knowledge exchange and approximating the learnings. Thus, through this survey one seeks for contributing with the professionals of health, especially those of Nursing both in the knowledge construction and in the care qualification to the patients with venous ulcers, aiming at the approaching of the professional wisdom to the popular wisdom. The research has as guiding question: What are popular care practices adopted by venous ulcer persons assisted at the angiology outpatient clinic of the Universitary Hospital of Santa Maria, Rio Grande do Sul, Brazil? And as goal: to know the popular care practices adopted by outpatients suffering from venous ulcer attended at the angiology ambulatory of the Universitary Hospital of Santa Maria, RS. This is a field research, which is qualitative, exploratory and descriptive, being developed at the clinic of the referring hospital and at venous ulcer people s household, in the period between December 2012 and March 2013. The research participants are adults and elderly with venous injury. These persons are being accompanied in this ambulatory. The data collection was carried out by a semi-structured interview. Afterwards, the data were transcribed and submitted to the content analysis. Ethical aspects were respected in accordance to the Resolution 196/96 of the National Health Council. The results are presented in an article format: Article 1: People are going to teach me the things and I do them! : popular practices in venous ulcer care; Article 2: Health care in outpatient people with venous ulcer. It can be evidenced that people resort to multiple alternatives in care, seeking for solving their health condition. Among the popular care practices referred by respondents, are: bless, pray, the use of plants and several types of tea, and pluralisms of practices. Besides these, there is the care with the nourishment, with injury and with the rest. Therefore, it is necessary that the health professionals, especially the nurses, know the population socio-cultural reality, which they attend, aiming at a congruent care.